1996
DOI: 10.1056/nejm199603213341202
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evidence of Alzheimer's Disease in Persons Homozygous for the ε4 Allele for Apolipoprotein E

Abstract: In late middle age, cognitively normal subjects who are homozygous for the epsilon 4 allele for apolipoprotein E have reduced glucose metabolism in the same regions of the brain as in patients with probable Alzheimer's disease. These findings provide preclinical evidence that the presence of the epsilon 4 allele is a risk factor for Alzheimer's disease. PET may offer a relatively rapid way of testing future treatments to prevent Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

58
810
6
14

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,244 publications
(893 citation statements)
references
References 36 publications
58
810
6
14
Order By: Relevance
“…Flory, Manuck, Ferrell, Ryan, and Muldoon (2000) extended these findings to middle-aged adults by showing that ApoE-ɛ4 carriers with a mean age of 46 had lower verbal memory performance than those with the ApoE-ɛ2 or ApoE-ɛ3 alleles. Also consistent with these results linking ApoE and cognition is the finding that the absence of the ApoE ɛ4 allele is associated with higher levels of cognitive functioning in very old (75-98 years) adults (Riley et al, 2000).However, some studies finding no differences in neuropsychological test performance as a function of ApoE genotype have also been reported (Plassman et al, 1997;Reiman et al, 1996; B. J. Small et al, 2000; G. E. Smith et al, 1998).…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Flory, Manuck, Ferrell, Ryan, and Muldoon (2000) extended these findings to middle-aged adults by showing that ApoE-ɛ4 carriers with a mean age of 46 had lower verbal memory performance than those with the ApoE-ɛ2 or ApoE-ɛ3 alleles. Also consistent with these results linking ApoE and cognition is the finding that the absence of the ApoE ɛ4 allele is associated with higher levels of cognitive functioning in very old (75-98 years) adults (Riley et al, 2000).However, some studies finding no differences in neuropsychological test performance as a function of ApoE genotype have also been reported (Plassman et al, 1997;Reiman et al, 1996; B. J. Small et al, 2000; G. E. Smith et al, 1998).…”
supporting
confidence: 55%
“…In a follow-up study, G. W. confirmed these findings in another sample of participants who had MCI but did not qualify for a diagnosis of dementia. In another study of individuals without dementia who were cognitively normal on neuropsychological evaluation, Reiman et al (1996) found that ApoE-ɛ4 homozygotes showed reduced rates of glucose metabolism in parietal, temporal, prefrontal, and posterior cingulate regions.Two studies using functional imaging have been reported. C. D. Smith et al (2000) carried out an fMRI study of object and face recognition in normal individuals.…”
mentioning
confidence: 96%
“…The reported decrease in glucose uptake mediated by stress or by high levels of GCs could place neurons in an energy-compromised environment, which could detrimentally affect neuronal responsiveness to pathophysiological events. In fact, glucose transport impairment precedes ATP depletion in brain, increasing neuronal vulnerability to excitotoxicity by compromising function of ion-motive ATPases (Mark et al, 1995), as it has been seen to occur in some neurodegenerative processes such Ab-induced toxicity, schizophrenia and others (Novelli et al, 1988;Kalaria and Harik, 1989;Sims, 1990;Mark et al, 1997;McDermott and De Silva, 2005) in which the reduction in glucose uptake occurs as an early step in the disease process prior to neuronal degeneration (Pettegrew et al, 1994;Reiman et al, 1996). On the other hand, GCs promote reduction in ATP levels (Tombaugh and Sapolsky, 1992;Lawrence and Sapolsky, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The impairment in glucose uptake and metabolism starts decades before classic AD symptoms and worsens steadily with disease progression 4, 5, 6. Studies using positron emission tomography with 2‐[(18)F]fluoro‐2‐deoxy‐D‐glucose (FDG‐PET) have demonstrated a characteristic pattern of hypometabolism, which is most pronounced in the posterior cingulate and medial parieto‐temporal cortices, also notable for their higher reliance on aerobic glycolysis relative to the rest of the brain 7, 8.…”
Section: Introductionmentioning
confidence: 99%